Predictors of Cardiac Complications of Abdominal and Small Pelvic Surgery in Elderly and Senile Patients - V. V. Moroz; O. R. Dobrushina; E. P. Strelnikova; A. N. Korniyenko; E. P. Zinina (Общая реаниматология)
In elderly and senile patients, extracardiac surgery frequently leads to cardiovascular complications. For their prevention, it is necessary to early detect patients with a potentially poor postoperative period. Routine preoperative examination is of limited prognostic value and instrumental techniques are inaccessible. Objective: to reveal the predictors of cardiac complications of abdominal and small pelvic surgery in elderly and senile patients. Subjects and methods. The study covered 82 patients (63 men and 19 women) aged over 60 years who had undergone at least one-hour open operations on the abdomen and small pelvis at the A. A. Vishnevsky Central Military Hospital Three in 2008—2011. In addition to routine procedures, the preoperative examination comprised the calculation of the Lee, Goldman, and Detsky scores and, in 35 patients, determination of NT-proBNP concentrations. Results. The logistic regression method applying the values routinely measured prior to surgery was used to make a cardiac complication-predicting model that included the Detsky index and blood glucose levels. Its dividing capacity proved to be satisfactory – AUC 0.75. Inclusion of echocardiographic data in the model failed to substantially improve its prognostic capacity. The cardiomarker NT-proBNP was the most effective predictor of postoperative complications. As its value became higher, there was an increase in the frequency of cardiac complications (p<0.001); AUC was 0.96. Conclusion. NT-proBNP is a highly effective predictor of postoperative complications in elderly and senile patients and may be included into preoperative screening. Key words: elderly and senile age, abdominal surgery, heart failure, surgery risk assessment, natriuretic peptides, Lee index, Goldman index, Detsky index, NT-proBNP.